Dermatofibrosarcoma Protuberans at Unusual Sites: A Case Series - Subrat Burma; Gayatri Rath (Journal of Clinical and Diagnostic Research, 2023)
Dermatofibrosarcoma Protuberans (DFSP) is a rare, locally aggressive malignant subcutaneous soft tissue tumour that often goes undiagnosed due to its indolent nature and non protuberant growth. Recurrences after surgical excision are a common issue. While the trunk and extremities are commonly affected sites, rarer locations such as the genitalia and breast have been reported. The rarity of the lesion, its occasional unusual presentation sites, the indolent yet locally aggressive nature, and the diagnostic and therapeutic challenges are the distinctive features of this tumour. This study presents three unusual sites of DFSP: scrotum, vulva, and pubic region, one of which is an uncommon variant known as pigmented DFSP (Bednar tumour).